Sosialisasi Mengenai Jalur Geotrek Tanjung Api Sebagai Salah Satu Situs Geowisata untuk Kelompok Sadar Wisata Desa Labuan Kabupaten Tojo Una-Una - Nunik Rezkiarti Janat; Muslimin U. Botjing; Risqa P. Mu’min; Tati Fitriana; Asrafil Asrafil; Riska Puspita; Irianto Uno (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The socialization program on the Tanjung Api Geotrek Route was carried out to enhance the understanding, awareness, and capacity of the Tourism Awareness Group (Pokdarwis) of Labuan Village in managing geotourism potential based on local geological heritage. The Tanjung Api area in Tojo Una-Una Regency, Central Sulawesi, is known for its natural fire phenomenon caused by the release of flammable natural gas, giving the site unique scientific, educational, and tourism value. Using a participatory approach, the program included material presentations, interactive discussions, the introduction of geotrek route design, and field observations at several potential geosites. The results show that participants’ knowledge increased by 80–90% regarding geotourism concepts, geological resource conservation, and strategies for developing interpretive educational geotreks. Participants also demonstrated strong enthusiasm to engage in destination management and benefit from the economic opportunities offered by tourism activities. This program serves as an initial step in strengthening collaboration between the community, academia, and local government to support sustainable geotourism development. The socialization provides a foundation for achieving independent, well-directed, community-based management of the Tanjung Api geosite as part of broader geotourism development in Tojo Una-Una Regency.